1988
DOI: 10.1677/joe.0.1160403
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous opioid peptide modulation of LH secretion in the ewe lamb: possible involvement of 5-hydroxytryptamine

Abstract: Evidence from several species suggest that the endogenous opioid peptides participate in the regulation of gonadotrophin and prolactin secretion. The aim of the present study involving intact and ovariectomized prepubertal ewe lambs was to compare the effects in vivo of an opioid peptide agonist [D-Ala2,N-Phe4,Met(0)ol5]-enkephalin (FK 33-824) and antagonist, naloxone, on concentrations of LH and prolactin in plasma, and levels of neurotransmitter metabolites in cerebrospinal fluid (CSF), with their effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1988
1988
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…This result agrees with studies in the rat where /?-endorphin increases prolactin levels (2) probably via the m u -or kappa-receptor (3,7). If similar receptors are involved in tllc control of prolactin secretion in the ewe, it then becomes dlfkxlt to explain why the mixed mu-and kappa-receptor agonist F K 33-824 does not increase prolaction secretion but does inhibit 1.H secretion in the ewe lamb (5). Presumably this may reflect differences in the ontogeny of the opioid receptors associated with LH and prolactin secretion during sexual maturation of the CWC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result agrees with studies in the rat where /?-endorphin increases prolactin levels (2) probably via the m u -or kappa-receptor (3,7). If similar receptors are involved in tllc control of prolactin secretion in the ewe, it then becomes dlfkxlt to explain why the mixed mu-and kappa-receptor agonist F K 33-824 does not increase prolaction secretion but does inhibit 1.H secretion in the ewe lamb (5). Presumably this may reflect differences in the ontogeny of the opioid receptors associated with LH and prolactin secretion during sexual maturation of the CWC.…”
Section: Discussionsupporting
confidence: 93%
“…/?-Endorphin in the ewe 125 to inhibit G n R H release. Certainly it has been shown that the opioid agonist FK 33-824 inhibits GnRH release from the isolated median eminence (5). Anatomical evidence can be used to support either possibility; the /?-endorphin terminals interact with the GnRH neurons in a t least two loci, the preoptic anterior hypothalamus and the median eminence (9).…”
Section: Intravenous /?-Endorphinmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, since catecholamines do not appear to be inhibitory prior to 22 weeks of age, some other neurotransmitter is probably holding LH in check during this period. This inhibitory neurotransmit ter may be an endogenous opioid, since opioid antagonists in crease LH release in prepubertal lambs [26][27][28], while opioid agonists inhibit LH [33,35]. Arguing against this possibility is the report that there was no change in response to the opioid antagonist, naloxone, between 9 and 27 weeks of age [28].…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that the inhibition of gonadotrophin secretion by opioids acts via the stimulation of the release of a precursor of melatonin, and other reproductively active pineal índoles (Reiter, 1984), 5-hydroxytryptamine (Stansfield et al, 1988). Similarly, the inverse relation¬ ship between prolactin and testosterone indicates short-day stimulation of testicular prolactin receptors in the hedgehog, the opposite of events in another hibernator, the hamster (Klemcke et al, 1983).…”
Section: Discussionmentioning
confidence: 99%